2014
DOI: 10.2459/jcm.0b013e328365c195
|View full text |Cite
|
Sign up to set email alerts
|

Impact of depression on circulating endothelial progenitor cells in patients with acute coronary syndromes

Abstract: We showed that ACS patients with MDE have a reduced number of circulating CD34CD133KDR cells compared with ACS patients without MDE, suggesting that the presence of MDE reduces the response of bone marrow to acute ischemic events. Considering the reparative role of EPCs in ACS patients, we propose that patients with MDE might be protected less than patients without MDE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“… 15 , 16 , 17 In this regard, there is recent evidence on reduced levels of circulating EPCs in patients with depression and acute coronary syndromes. 18 , 19 Oxidative stress, measured by circulating markers (superoxide dismutase, glutathione, oxLDL, among others) in plasma and platelets, 10 vascular relaxation 20 and animal models, 21 , 22 has been closely associated with major depression. 23 , 24 Studies in a depression model with chronic mild stress rats demonstrated associations between endothelial dysfunction, oxidative stress and depression-like symptoms that were modulated by chronic SSRI.…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 16 , 17 In this regard, there is recent evidence on reduced levels of circulating EPCs in patients with depression and acute coronary syndromes. 18 , 19 Oxidative stress, measured by circulating markers (superoxide dismutase, glutathione, oxLDL, among others) in plasma and platelets, 10 vascular relaxation 20 and animal models, 21 , 22 has been closely associated with major depression. 23 , 24 Studies in a depression model with chronic mild stress rats demonstrated associations between endothelial dysfunction, oxidative stress and depression-like symptoms that were modulated by chronic SSRI.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, individuals with anxiety disorders showed a significant lower number of circulating EPCs compared to subjects without mood or anxiety disorders. Cross‐sectional dimensional measurements of depression and anxiety also indicated that high scores at both HAM‐D and HAM‐A were related to depletion of EPCs, corroborating our previous preliminary observations (Di Stefano et al ., ). Overall, our data are in line with those of Dome et al .…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, EPCs may play an important role in the molecular background of depression‐associated cardiovascular morbidity. In a preliminary study, we have shown that major depression decreases EPC levels in ACS patients compared with healthy individuals and patients with current MDE without a history of cardiovascular diseases (Di Stefano et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…LVM refers to the pathological changes in the immune activation state of the body caused by large amounts of cytokines secreted by myocardial cells, under the influence of injury, ventricular wall stress, oxidative stress and partial activation of the neuroendocrine system, which induces myocardial collagen deposition and changes in collagen type and collagen degradation (4). Recent studies on LVM reported the presence of stem cells in the myocardium, which have the ability to differentiate into various cells (5,6). A small number of stem cells are able to express c-kit and nanog surface markers.…”
Section: Introductionmentioning
confidence: 99%